Before 6 years the father was 3 times older than his son,after 6 years he will be 2 times older.How many years old are the father and the son?

2
the statements should be that: Father was 3 times as old as the Son.... and he will be 2 times as old as his son.. We should not use " older than".
I don't know,but that is how we learnt in school.
but unfortunately, that is not correct way of saying..
ok

Answers

The Brainliest Answer!
2015-04-23T23:20:36+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let f = father's age
Let s = son's age

Before 6 years :
f-6 = 3(s-6)\implies f=3s-12

After 6 years :
f+6 = 2(s+6)\implies f=2s+6

Subtract second equation from first:
0=s-18\\s=18

Plug this in second equation and get:
f=2(18)+6\\f=42

Therefore the father is 42 years old and the son is 18 years old
2 5 2
2015-04-23T23:57:43+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the present (current) ages of father and son be  F  and  S  years.  We need to form two equations in F and S and then solve them.

      Father was 3 times older than his son, 6 years earlier.  Actually this statement should be that  Father was 3 times as old as  the son.  6 years ago, their ages were F-6 years and  S-6 years respectively.

         =>  F - 6 =  3 *  (S - 6)     --- (1)

     After  6 years from now, father will be 2 times as old as his Son. After 6 years their ages are F+6 years and S+6 years respectively.

         =>  F + 6  = 2 * (S + 6)      --- (2)

subtract (2) from (1), we get

                - 12 = S - 30      =>    S = 18 years
 Using equation (1) ,   we get,   F - 6 = 3 * (18-6) = 36

        Hence,   F = father's age = 42 years.    
             and son's age = 18 years.

3 5 3